Aluminum and magnesium metal matrix nanocomposites. ([2017]) - Ceschini, Lorella; Dahle, Arne; Gupta, M (Manoj); Jarfors, Anders Eric Wollmar; Jayalakshmi, S; Morri, Alessandro; Rotundo, Fabio; Toschi, Stefania; Singh, R. Arvind
No abstract available